2021
DOI: 10.1111/petr.13986
|View full text |Cite
|
Sign up to set email alerts
|

SARS‐CoV‐2 and pediatric solid organ transplantation: Current knowns and unknowns

Abstract: The COVID‐19 pandemic has proven to be a challenge in regard to the clinical presentation, prevention, diagnosis, and management of SARS‐CoV‐2 infection among children who are candidates for and recipients of SOT. By providing scenarios and frequently asked questions encountered in routine clinical practice, this document provides expert opinion and summarizes the available data regarding the prevention, diagnosis, and management of SARS‐CoV‐2 infection among pediatric SOT candidates and recipients and highlig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 139 publications
(238 reference statements)
0
1
0
Order By: Relevance
“…Data of pediatric patients who underwent solid organ transplantation showed that immunosuppression was not an additional risk factor for severe or complicated COVID-19, showing that most had mild or moderate disease severity like the general population. 42,[48][49][50][51][52]…”
Section: Covid-19 In Immunosuppressed Children With Neuromuscular Dis...mentioning
confidence: 99%
“…Data of pediatric patients who underwent solid organ transplantation showed that immunosuppression was not an additional risk factor for severe or complicated COVID-19, showing that most had mild or moderate disease severity like the general population. 42,[48][49][50][51][52]…”
Section: Covid-19 In Immunosuppressed Children With Neuromuscular Dis...mentioning
confidence: 99%